Rekonstruksi Identitas Naratif Ricoeurian Etnis Tionghoa melalui Ingatan Kudus Volfian demi Indonesia yang lebih Baik - Tobing, David (MELINTAS An International Journal of Philosophy and Religion (MIJPR), 2020)
In Indonesia’s history as a nation, Chinese ethnicity has been victimised, especially during the transitions of power occured in this nation. Among others, the incidents are the 1965 tragedy which signifies transition from “Orde Lama” to “Orde Baru”, and the May 1998 riot which signifies transition of power from “Orde Baru” to Reformation Order. Referring to the incidents, this article analyses the roots of the problem and sees the possibilities to prevent them to happen again. The author of this article presents an argument and a suggestion as follows. First, Chinese ethnicity has become the victim because of a ‘dark’ narration that constructs a narrative identity of the ethnicity as a victim or a wounded self—this dark narration seems to justify the discriminative actions directed to the Chinese individuals. Second, one can respond to this problem by reconstructing a Ricoeurian narrative identity as the form and a Volfian sacred memory as the content, in order to transform the Chinesse narrative identity from a victim or a wounded self into a survivor or a healing self.